SEARCH FOR EXISTENCE IN SHARI SPRINGER BERMAN’S THE NANNY DIARIES MOVIE (2007): AN EXISTENTIALIST APPROACH - INDRAWATI, INDRAWATI (2010)
This study is aimed to show search for existence in The Nanny Diaries movie by using existentialist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the existentialist approach.